Developing Flipbook-Based on Competency for Vocational High School Teacher - Nasution, Yeni Puspitasari; Rizal, Fahmi; Irfan, Dedy; Refdinal, Refdinal; Sari, Adha Kurnia (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to improve the quality of learning in vocational high schools by strengthening teachers' teaching skills as a learning tool, encouraging innovation in teaching methods and providing a competency development model for vocational school teachers. This research uses research methods (Research Development) with the 4D Define, Design, Development, Disseminate model. This research method provides a systematic approach that includes steps and focuses on the process of developing teacher competency effectively to ensure that the flipbook developed is relevant to practical and contextual needs. The 4D model provides a planned testing and evaluation framework, so that research can provide strong empirical evidence about the success of the learning model being developed. The first stage is to determine the needs and objectives of developing the flipbook, which is then continued by designing the concept and structure of the flipbook in accordance with the curriculum and teaching needs of vocational school teachers. After that, the development team carried out the flipbook development process based on a predetermined design, by carrying out regular trials and revisions. The final step is to socialize the flipbook to vocational school teachers and distribute it to relevant stakeholders. The research results obtained in the media validation test were 86%, material 88% and language 89%. The Practicality Assessment obtained a score of 89% and classical completeness 100%. It was concluded that this medium for developing vocational teacher competency is effective as a reference choice in developing vocational teacher competency.